A transição da consciência para a consciência-de-si na Fenomenologia do Espírito de Hegel. - Tortato, Christiano (2016)
Hegel’s Phenomenology of the Spirit presents itself divided into eight chapters, which find themselves harmonically structured in three sections: A – Consciousness, composed by three chapters in which the first three levels of the consciousness are investigated: Sensible Certainty, Perception and Understanding; B – Self-Consciousness, composed by a chapter entitled The truth about the certainty of yourself; and C – Spirit, composed by four chapters, Certainty and the true reason, The Spirit, The Religion and the Absolute Knowledge. Our work has as its main objective to investigate the transition made by the consciousness towards the self-consciousness as from a reflection about the dialectics method of exposition adopted by Hegel. In this perspective we’ll represent the arduous trajectory made by the consciousness as from the varied levels of experience that he stablishes with his objects in the unrolling of the first four chapters of Phenomenology. We will follow all the development of the consciousness presented in the first section, centralizing our investigation to the self-consciousness possible. In other words, we search the determinations that make the transition of the consciousness possible, that in a first moment presents itself immersed in a sensible and perceptible world characterized by the knowledge-of-another-one, for a second moment, a moment in which the consciousness starts to relate to another consciousness and only in this way presents itself with the determination of the knowledge-of-oneself.